2023
DOI: 10.1021/acscentsci.2c01373
|View full text |Cite
|
Sign up to set email alerts
|

How Segmental Dynamics and Mesh Confinement Determine the Selective Diffusivity of Molecules in Cross-Linked Dense Polymer Networks

Abstract: The diffusion of molecules ("penetrants") of variable size, shape, and chemistry through dense cross-linked polymer networks is a fundamental scientific problem broadly relevant in materials, polymer, physical, and biological chemistry. Relevant applications include separation membranes, barrier materials, drug delivery, and nanofiltration. A major open question is the relationship between transport, thermodynamic state, and penetrant and polymer chemical structure. Here we combine experiment, simulation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
47
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(56 citation statements)
references
References 77 publications
5
47
0
Order By: Relevance
“…The research on nanoparticle hopping diffusion in crosslinked polymer networks may be extended to glass forming polymer network, an cutting-edge research topic with applications such as separation membranes, barrier materials, and nanofiltration as the technological background. A recent joint theory-experiment-simulation study 193 on the diffusion of large aromatic molecules ("penetrants") in dense cross-linked polymer networks demonstrated that the motion of the penetrants is primarily determined by the coupling of local penetrant hopping to polymer structural relaxation, with the entropic mesh confinement effects being of secondary importance. More aspects of nanoparticle hopping in crosslinked networks have been revealed by molecular simulations.…”
Section: Discussionmentioning
confidence: 99%
“…The research on nanoparticle hopping diffusion in crosslinked polymer networks may be extended to glass forming polymer network, an cutting-edge research topic with applications such as separation membranes, barrier materials, and nanofiltration as the technological background. A recent joint theory-experiment-simulation study 193 on the diffusion of large aromatic molecules ("penetrants") in dense cross-linked polymer networks demonstrated that the motion of the penetrants is primarily determined by the coupling of local penetrant hopping to polymer structural relaxation, with the entropic mesh confinement effects being of secondary importance. More aspects of nanoparticle hopping in crosslinked networks have been revealed by molecular simulations.…”
Section: Discussionmentioning
confidence: 99%
“…A single exponential function is observed, in distinction to probe diffusion in linear polymers which typically exhibits a Williams–Landel–Ferry (WLF) or nonexponential temperature relationship when approaching T g / T = 1. ,, However, temperature relationships derived here are a result of changing T g with cross-link density, not the experimental temperature. A single exponential form has been observed in experiment, theory, and simulations of dye diffusion in polymers for a broad range of penetrant volumes . The reduction in diffusion coefficient is generally attributed to a slowing down of the segmental dynamics (increased T g ) as well as an entropic mesh confinement term .…”
mentioning
confidence: 88%
“…Analogous ethylene networks were prepared with a fast cross-linker reported in prior work and investigated by us for probe diffusion in acrylic vitrimers . The neighboring nitrogen groups accelerate the rate-limiting proton transfer step of the boronic transesterification and increase the exchange rate by a factor of ∼10,000 . The faster cross-linker has six carbons connecting the boronic acids, and thus we only prepare the C 6 network for these comparisons (Scheme ).…”
mentioning
confidence: 99%
See 2 more Smart Citations